Lawmaking through translation: 'translating' crimes and punishments - Oner, Senem; Karadag, Ayse Banu (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2016)
This article examines the role translation played in the encounter between legal systems through the examination of the Ottoman Penal Code (1858), which was drafted using the French Penal Code (1810) as the source. The results obtained through the comparative textual analysis of the codes in Ottoman Turkish and French are discussed with respect to the historical/legal circumstances pertinent to the Ottoman modernization/westernization in the Tanzimat (Reorganization) Period. Adherence to the source text norms observed in the translation of the articles on 'crimes against the state and their punishment' is argued to reflect the role the Ottoman Code was expected to play in the modernization of the Ottoman Empire. Adherence to the target culture/system norms observed in the translation of the articles on 'crimes against individuals and their punishment' is argued to reflect the ongoing power of the then-existing Islamic Ottoman penal law system. It is also claimed that the Ottoman Code belonged to the 'translated law' system in the Ottoman-Turkish 'legal polysystem'. Re-thinking the original-translation binary opposition in the context of the Ottoman Code, it is suggested that the Ottoman Code was a translation which was not produced to be presented/perceived as a translation but so as to entertain the status of an original code in the target system where the translated code was the law itself and had legal binding power. Thus the Ottoman Code functioned both as original and as translation and no power relationship existed between the Ottoman Code and the French Code in terms of their statuses in their respective systems/for their respective audience. Consequent to the observed dynamics of the case in question, in the study lawmaking through translation has been suggested as an alternative term to 'legal translation' to explain the specific relationship between making a law and translation where the latter is used as an instrument for the former.
Keywords: lawmaking through translation; translated law; legal polysystem; original/translation binarism; translation history; law history; legal encounter; Linguistics